Rubrivivax gelatinosus biomass as an immunostimulant for pacu Piaractus mesopotamicus - Gallani, Silvia Umeda [UNESP]; Ramos Valladao, Gustavo Moraes [UNESP]; Giglio Ponsano, Elisa Helena [UNESP]; Pilarski, Fabiana [UNESP] (Wiley-Blackwell, 2017)
Rubrivivax gelatinosus is a bacterium present in the environment successfully used for treatment of fish industry effluent. Besides cleaning the effluent, this bacterium provides a biomass rich in proteins and carotenoid as a metabolic product. This study describes for the first time the use of this biomass asan immunostimulant feed. Haematological, immunological, biochemical and growth parameters in pacu Piaractus mesopotamicus fed control diet or diets supplemented with 0.5 or 1.5gkg(-1) of the R. gelatinosus biomass during 60days were assessed. Fish were sampled at 0, 30 and 60days. The inclusion of increasing levels of biomass in feed increased thrombocytes and neutrophils (P<0.05) and decreased lymphocytes (P<0.05) as well as activated the complement system (P<0.05). Glucose levels, hepatosomatic index and weight were positively affected by the inclusion of R. gelatinosus biomass (P<0.05). The use of R. gelatinosus biomass in feed improved the immune response of fish through the enhancement of some phagocytic cells, reduced time to activation of the complement system and increased growth parameters. This study reveals a promising use for a by-product resulted in the wastewater treating in aquaculture.
Keywords: aquaculture; carotenoid; effluent treatment; fish; haematology; immunology